THE ROLE OF FINTECH IN TRANSFORMING GLOBAL FINANCE - Lagalur, Erappa Ramappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The financial services industry is experiencing a transformative shift driven by the rapid growth and adoption of financial technology, or fintech. Fintech represents the integration of innovative digital technologies into financial services, revolutionizing how money is managed, transferred, invested, and regulated globally. This paper examines the pivotal role of fintech in transforming the global financial landscape by exploring its origins, key technological enablers, and the wide-ranging impacts on traditional financial institutions, consumers, and regulators. Fintech innovations have democratized access to financial services, enhanced operational efficiency, reduced costs, and improved customer experiences. Technologies such as mobile payments, blockchain, artificial intelligence, and peer-to-peer lending platforms have reshaped sectors including banking, insurance, wealth management, and regulatory compliance. Moreover, fintech has played a significant role in promoting financial inclusion, particularly in developing economies where traditional banking infrastructure is limited. The adoption of mobile money services has empowered millions to participate in the financial system for the first time. This paper also discusses the challenges associated with fintech adoption, such as data privacy concerns, cybersecurity risks, regulatory complexities, and the digital divide. It highlights the importance of balanced regulation and collaboration between fintech startups and traditional financial institutions to ensure sustainable growth. Additionally, the emergence of decentralized finance and green fintech exemplifies how the sector continues to innovate, addressing evolving economic and environmental priorities. In conclusion, fintech is not merely a technological advancement but a fundamental reimagining of global finance, creating opportunities for efficiency, inclusivity, and sustainability. By addressing its challenges responsibly, fintech can pave the way for a more equitable and resilient financial ecosystem that benefits individuals, businesses, and governments worldwide.